Предмет: Математика,
автор: varusyasorokina
(x-3)x(x+3)-(x-2) 2 якщо х=-1
БИСТРОЛ
Ответы
Автор ответа:
0
Ответ:
-17
Пошаговое объяснение:
(х - 3)(х + 3) - (х - 2)² =
(х² + 3х - 3х - 9) - (х² - 4х + 4) =
(х² - 9) - (х² - 4х + 4) = х² - 9 - х² + 4х - 4 = 4х - 13
х = -1
4х - 13 = 4 * (-1) - 13 = -4 - 13 = -17
Похожие вопросы
Предмет: Українська мова,
автор: Аноним
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: География,
автор: kovalenkokarolina987
Предмет: Математика,
автор: BangtanSoneantan
Предмет: Математика,
автор: polly200777hhh